Handling an Isolated Malleus Handle Fracture: Current Diagnostic Work-up and Treatment Options. (March 2015) - Delrue, Stefan; De Foer, Bert; van Dinther, Joost; Zarowski, Andrzej; Somers, Thomas; Casselman, Jan; Offeciers, Erwin
Background: An isolated malleus handle fracture is rare and presents with vague otological symptoms. Diagnosis depends on careful history taking and otoscopic examination. Different treatment options are available. Reconstruction with hydroxyapatite bone cement is a relatively new technique. Objective: The aim of this article is to review the current diagnostic work-up and treatment options and to demonstrate our method of treatment with hydroxyapatite bone cement. Methods: Three cases, repaired with hydroxyapatite bone cement in a tertiary referral otologic center, were retrospectively analyzed. A review of the literature on diagnosis and treatment procedures was performed. Results: One fracture occurred by withdrawing a finger from the external auditory canal and 2 occurred without clear prior trauma. Our 3 cases were successfully repaired with hydroxyapatite bone cement. Conclusion: Diagnosis of an isolated malleus handle fracture still depends on careful clinical examination. In addition to pure tone audiometry, both low and higher frequency tympanometry may be useful. High resolution computed tomography with reformatting through the malleus handle is the most accurate imaging modality. Reconstruction with hydroxyapatite bone cement is reliable by restoring the original situation with only minimal manipulation and without additional ossicular interruption.